MISSIONARIES AND COLONIALISM: The Nineteenth Century British and Contemporary Korean Missionaries in Zambia - Hyunwoo Koo (Scriptura Indonesia, 2020)
There are about ten Korean missionaries in Zambia, which is Christianized since experiencing colonial era under Western Christians. This situation brings a question regarding to their uniqueness compare to the nineteenth-century-British missionaries: how are these Korean missionaries distinct from Western evangelists and what has shaped this difference? To answer the question, this article compares several groups of missionaries by consulting historical records, established literature, and interviews produced by author. Especially, voices from the Korean missionaries in Zambia reveal the distinctiveness of themselves as the people who share the experience of living under colonial rule, and suggest their role within Zambian Christianity and society.